Performance Analysis for Bit-Error-Rate of DS-CDMA Sensor Network Systems with Source Coding - Ali M. Fadhil; Haider M. AlSabbagh (Universitas Ahmad Dahlan, 2012)
One of the distinguished techniques used with wireless sensor networks to access the network is utilizing direct sequence-code division multiple access. However, amount of consumed energy and multiple access interference are still considered as the main problems with employing such networks. The consumed energy and interference are rising when number of users (receivers) increases. Therefore, this paper is conducted to investigate mitigating influence these factors through analyzing the minimum energy coding which exploits redundant bits for saving power with employing radio frequency link and on-off-keying modulation. These factors are analyzed and discussed for several levels of expected errors in the utilizing channel, through the bit error rates and amount of signal to noise ratio for different number of users.